Performance of EGZrO2-EGFe2O3/HY as photocatalyst and its efficacy in decolorization of dye-contaminants. - Muhammad Farhan, Hanafi; Norzahir, Sapawe; Mohd Zulkhairi, Abdul Rahim; Nurul Nabihah, Rahman; Abu Hassan, Abd Rahman; Asimi Ana, Ahmad (Malaysian Society of Analytical Sciences (ANALIS), 2016)
The performance of electrogenerated metals supported on HY zeolite (EGZrO2-EGFe2O3/HY) was studied under sunlight irradiation for the decolorization of methylene blue (MB) and Congo red (CR) in aqueous solutions. The prepared photocatalysts were examined using X-ray diffraction (XRD), transmission electron microscopy (TEM), and Brunnauer-Emmett-Teller surface area analysis (BET). An amount of 0.375 g L-1 EGZrO2-EGFe2O3/HY was found to be the optimum dosage for 10 mg L-1 dyes, which gave almost complete photodecolorization of both MB and CR dye after 2 hours of contact time at pH 9 and pH 7, respectively. In addition, a control experiment was also conducted under similar conditions to confirm the efficacy of the prepared photocatalyst. The simple preparation of the photocatalyst and low amount of metal loading required, with simultaneously existence of synergistic effect from both metal oxides exhibits the great potential of the system that could be applied in textile or other industries wastewater treatment.